Comparative studies on combustion, performance and emission characteristics of a two-wheeler with gasoline and 30% ethanol-gasoline blend using chassis dynamometer. (5th January 2019) - Sakthivel, P.; Subramanian, K.A.; Mathai, Reji
Highlights: E30 offers high RON (1 0 0), better RVP and water tolerance characteristics. Vehicle power decreased by 10%; fuel consumption increased by 5% with E30 in WOT. CO and HC emissions decreased by 75% and 66% with higher NOx emission in WOT test. CO and NOx emissions decreased by 56% and 38% with moderate increase in HC in IDC. Effect of E30 was mainly due to change in operating conditions and enleanment effect. Abstract: Mid-level ethanol-gasoline blends such as E30 offers significant advantages in terms of higher octane number, desirable Reid vapor pressure and water tolerance characteristics compared to lower blends. An experimental study was undertaken on a motorcycle with commercial gasoline (E0) and 30% ethanol blended gasoline (E30) using a chassis dynamometer. Combustion, performance and emissions characteristics were investigated under steady state (wide-open throttle – WOT) and transient (Indian driving cycle – IDC) operating conditions. In the WOT test, carbon monoxide and hydrocarbon emissions decreased however oxides of nitrogen (NOx) increased with E30 compared to E0. The specific fuel consumption was higher with E30 but vehicle power decreased. Combustion analysis showed an increased combustion duration and delay in heat release rate with E30. The peak combustion pressure and maximum rate of pressure rise were also lower. Mass emission studies over IDC test show a decrease in CO and NOx emissions with E30 while hydrocarbon emission increased marginally. The notable point emerged from the study is that the operating conditions and change in air-fuel mixture regime impact the performance and emissions of two-wheeler significantly. The present work provides useful information for designing a dedicated spark ignition engine suitable for mid-level ethanol blends.